The South Beach heart health revolution : cardiac prevention that can reverse heart disease and stop heart attacks and strokes - Agatston, Arthur (New York : St. Martin's Griffin, 2008)
Introduces a program emphasizing a preventative rather than a therapeutic attitude toward cardiac health, detailing four key elements--heart-healthy eating, functional fitness, advanced blood test and heart imaging, and protective medications.
Reprint. Originally published as: The South Beach heart program. [Emmaus, Pa.?] : Rodale, c2007.
Includes bibliographical references (p. 267-282) and index.
Keywords: Coronary heart disease -- Prevention; Coronary heart disease -- Treatment; Heart -- Prevention. -- Prevention; Medicine, Preventive